Dampak Teknologi AI pada Tren Ketenagakerjaan: Peluang dan Tantangan Masa Depan - Ganteng, Raihan (Maliki Interdisciplinary Journal, 2025)
This article examines the impact of artificial intelligence (AI) technology on employment trends across various economic sectors. Using a literature review method, it explores opportunities such as operational efficiency and new job creation, alongside challenges like job automation that may replace human roles. The findings indicate that AI has significant potential to drive economic growth while posing social risks. This article provides strategic recommendations to support workforce adaptation to changes driven by AI, emphasizing the importance of collaboration among stakeholders to create an inclusive employment ecosystem amidst rapid AI advancements. exploring the specific impacts of AI in certain sectors, such as education, health, and energy. In addition, in-depth studies of workers’ adaptation strategies in developing countries are also important to ensure a just transition.